A short description of the issue of reprivatizing property of the Church in Romania with particular focus on the case of Mikó Székely College - VERESS, EMŐD (The Opole Studies in Administration and Law, 2022)
The „communist“ regime nationalized church property also in Romania. Minority (Hungarian and German) churches were traditionally extensively involved in school maintenance and were particularly hard hit. In the interwar period, these schools provided education in minority languages. Nationalization affected the entire property of the denominational schools and often broke centuries of tradition. The property included school buildings, teachers' residences, and economic assets that served to finance the school. After the regime change, the state gradually established a framework for restitution. Still, after a positive start, the trend was reversed and restitution of the nationalized property to churches, without any change in the legal framework, began to be prevented by administrative and judicial practice. Through a concrete example, the article illustrates the contradictions in case law, the ideological obstacles to restitution, and the complex legal history and civil law issues that arise.